Trends in National R&D Projects on Biomimetics in South Korea - Hyein Na; Eunhee Kim (Biomimetics)
Imitating nature’s mechanisms has enormous potential to improve our lives and tools. Biomimetics emulates nature’s proven patterns and strategies to develop novel solutions widely applied in various fields. This study aims to propose an overall perspective and research direction for innovation using biomimetics. Using text network analysis and topic modeling, we analyzed the evolution of 5202 Korean R&D projects in biomimetics. The results indicate significant interdisciplinary collaborations between bioengineering, drug development, polymer chemistry, and robotics. Moreover, biomimetic national R&D has primarily focused on fundamental research and its trends reveal interconnection with topic clusters around intelligent robotics, biomedical engineering, and materials science. This study provides guidelines for governments and R&D organizations to establish biomimetic R&D plans and select convergence topics for innovation.